Evaluatıon Of Pulpal Hıstologıcal Changes Due To Rapıd Palatal Expansıon - Fulya Kayhan; Dilaver Demirel; Nazan Küçükkeleş; Hakan Çermik; Sevgi Küllü (Galenos Yayinevi, 1997)
This study was carried out to investigate pulpal changes occurring with the use of heavy forces, created by rapid palatal expansion appliances. Arcylic cap splint appliance is a type of rapid palatal expansion appliance which maintains the control of the vertical proportions, eliminates the influences of occlusion and provides maximum tooth support. Ten study and 10 control, a total of 20 teeth were examined histologically under light microscopy. Circulatory disturbances, disruption of the odontoblastic layer, signs of dentinal depositing and central fibrosis were observed as a result of the heavy forces acting on the anchor teeth. No contrariety was seen among buccal and lingual sights of the pulp in both of the study groups.